African views of the West. - White, Jo Ann (New York, J. Messner, 1972)
Essays reflecting the reactions of the African people to western influences during the pre-colonial, colonial, and neo-colonial periods.
Keywords: Africa -- Civilization -- Western influences -- Juvenile literature; Africa -- Civilization -- Western influences